2017
DOI: 10.21273/hortsci11412-16
|View full text |Cite
|
Sign up to set email alerts
|

Managing Apple Crop Load and Diseases with Bloom Thinning Applications in an Organically Managed ‘Honeycrisp’/‘MM.111’ Orchard

Abstract: Additional index words. apple scab, cedar apple rust, Japanese knotweed, liquid lime sulfur, powdery mildew, quince rust Abstract. Although demand for organic produce continues to increase in the midAtlantic, few apple (Malus 3domestica Borkh.) growers in the region have adopted organic management practices due to the considerable disease, insect, and weed pressure, as well as the lack of effective crop load management tools. In this study, lime sulfur (LS) and Regalia Ò (R) were applied in different sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…This study demonstrated that use of the 'Gala' PTGM reduced fruit set, yield, fruit number, and estimated yield per acre at both sites in most cases (Tables 2-4). This is in agreement with other research studies [18,25] which demonstrate that the PTGM is a reliable method for timing blossom thinning sprays. Additionally, lime sulfur sprays applied at 20% open bloom and 48 h later performed near equally well as the PTGM treatment in reducing fruit set, crop density, kg fruit/tree, fruit no/tree, and estimated yield per acre in most situations.…”
Section: Fruit Set and Yield As Affected By Thinning Spray Timingsupporting
confidence: 93%
See 1 more Smart Citation
“…This study demonstrated that use of the 'Gala' PTGM reduced fruit set, yield, fruit number, and estimated yield per acre at both sites in most cases (Tables 2-4). This is in agreement with other research studies [18,25] which demonstrate that the PTGM is a reliable method for timing blossom thinning sprays. Additionally, lime sulfur sprays applied at 20% open bloom and 48 h later performed near equally well as the PTGM treatment in reducing fruit set, crop density, kg fruit/tree, fruit no/tree, and estimated yield per acre in most situations.…”
Section: Fruit Set and Yield As Affected By Thinning Spray Timingsupporting
confidence: 93%
“…Lime sulfur effects on fruit russeting has varied between different studies and is likely dependent on multiple factors. Stopar [30] found that increasing concentrations of lime sulfur did not increase the occurrence of fruit russet, whereas Peck et al [25] found that model-guided lime sulfur blossom thinning sprays resulted in a significant increase of fruit russet incidence. The adjuvant used in lime sulfur sprays can also have significant impacts on fruit russet incidence [29].…”
Section: Effects Of Thinning Timing Strategies On Fruit Quality Packout and Phytotoxicitymentioning
confidence: 99%
“…The reduction of fruits per tree (crop load) in bloom-thinned trees is due to the lime sulfur-induced reduction in the number of fruits within each fruiting cluster. Similar results were also reported in previous studies (Yoder et al, 2013;Peck et al, 2017). Additionally, a recent study reported significantly larger fruit weight and size in bloom-thinned trees at harvest, along with a lower yield and number fruits per tree, compared with untreated trees (Allen et al, 2021).…”
Section: Effect Of Bloom Thinning On the Number Of Fruits Per Tree Yi...supporting
confidence: 90%
“…The application timing of thinning in apple trees is important to achieve the optimum result (Jones et al, 1992;Dennis, 2000;Guak et al, 2004), and the earlier thinning time was more effective than the later thinning time (Bayers and Carbaugh, 2002;Allen et al, 2021). In general, lime sulfur thins flowers by inhibiting pollen germination, pollen tube growth, and fertilization (Peck et al, 2017;Schupp and Kon, 2019). Inconsistent bloom thinning responses may be attributed to application timing since pollen tubes can reach the base of the style within 48 hours (Yoder et al, 2009).…”
Section: Effect Of Bloom Thinning On the Fruit Set Ratementioning
confidence: 99%
See 1 more Smart Citation